Efek Senam Lanjut Usia Terhadap Peningkatan Aktifitas Fisik Lanjut Usia Di Dusun Bonorejo Kelurahan Plesungan - Saelan Saelan; Galih Setia Adi; Sahuri Teguh Kurniawan; Kukuh Ardian (Wiraraja Medika : Jurnal Kesehatan, 2020)
The problem that often arises in the elderly is the lack of physical activity that is less affect the elderly health condition. These activities can increase the ability of the activity and can improve fitness because the elderly are needed mild activities to train the work of the heart that has decreased Gymnastics will help the body stay fresh and fit because it keeps the bones strong, encourages the heart to work optimally, and removes free radicals in the body. It is necessary to conduct elderly gymnastics research on the health of elderly Physical Activity at Posyandu Lansia of Bonorejo, Plesungan Village. The purpose of this study was to analyze the effect of elderly gymnastics on the health of the elderly physical activity. Experimental research methods with One Group Design Pre-test and Post-test techniques. Purposive sampling was used to determine its samples. It is a technique of determining the sample among the population through the researcher wants. The number of the sample was 30 respondents. The sample criteria were the elderly aged 60 years and over and did not have physical health problems. Measurement of physical activity health applied a walk test for 6 minutes. The pre-test measurement result in the treatment group showed 14 respondents (46.7%) could walk for 6 minutes and 16 respondents were unable to walk for 6 minutes. The post-test measurement revealed 28 respondents (93.3%) could walk for 6 minutes and 2 respondents (6.7%) were unable to walk for 6 minutes. Bivariate test with Wilxocon in the intervention group obtained p-value of 0.001 <0.05 Ho is rejected Ha is accepted meaning that there are effects of Elderly Gymnastics Against Increased Physical Activity of Elderly. Research can be used as a reference in applying non-pharmacological therapy in the form of gymnastics in the elderly to improve health in the elderly.